Proceedings of the 52nd Annual Meeting of the Association for Computational Linguistics (Volume 2: Short Papers) 2014
DOI: 10.3115/v1/p14-2045
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Recognizability of Syntactic Relations Using Contextualized Examples

Abstract: A common task in qualitative data analysis is to characterize the usage of a linguistic entity by issuing queries over syntactic relations between words. Previous interfaces for searching over syntactic structures require programming-style queries. User interface research suggests that it is easier to recognize a pattern than to compose it from scratch; therefore, interfaces for non-experts should show previews of syntactic relations. What these previews should look like is an open question that we explored wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…To better convey the meaning of the words in the pattern, we also showed up to 5 substitute words for each word in the pattern. Previous research observed that offering example words and sentences helps disambiguate syntactic search queries (Muralidharan and Hearst 2014). Hence, we gave annotators four unannotated documents, of which exactly one did not contain the pattern.…”
Section: Interpretability Of Senpaimentioning
confidence: 99%
“…To better convey the meaning of the words in the pattern, we also showed up to 5 substitute words for each word in the pattern. Previous research observed that offering example words and sentences helps disambiguate syntactic search queries (Muralidharan and Hearst 2014). Hence, we gave annotators four unannotated documents, of which exactly one did not contain the pattern.…”
Section: Interpretability Of Senpaimentioning
confidence: 99%